A Clinical Test to Measure Airborne Microbial Contamination on the Sterile Field During Total Joint Replacement: Method, Reference Values, and Pilot Study. Issue 3 (25th September 2018) - Harp, John H.
Abstract : Background: Airborne microbe-carrying particles in the operating-room environment during total joint replacement are a risk factor for periprosthetic joint infection. The present study focuses on a simple environmental test, based on practices used in aseptic cleanrooms, to quantify the deposition of microbe-carrying particles onto the sterile field. Methods: Settle plates are exposed Petri dishes. A settle plate test system and sampling plan were developed from current practices used in aseptic manufacturing. A pilot study evaluated this system in an orthopaedic operating room during 22 total knee and hip arthroplasties. The microbial deposition total (MDT), expressed in colonies/m 2, is proposed as an outcome variable to report airborne sterile-field contamination as measured with settle plates. Two reference MDT levels were developed: (1) an upper limit of 450, corresponding with the ultraclean air definition of 10 colonies/m 3, and (2) a target level of 100, corresponding with 1 colony/m 3 . These levels also correspond with widely used limits in aseptic cleanrooms and controlled environments. Results: High MDT standard deviations were noted. Ninety-one percent (95% confidence interval, 71.0% to 98.7%) of wound zone MDT levels were within the upper limit. Twenty-seven percent (95% confidence interval, 12.9% to 48.4%) of wound zone levels were within the target level. Conclusions: Settle plates are a feasible technique to test environmental levels of microbe-carrying particles on sterile fields during total joint replacement for scientific and environmental quality studies. Clinical Relevance: This settle plate operating-room environmental test can be used in future research to validate the presence of actual ultraclean-air conditions during periprosthetic joint infection outcome studies. Surgeons also can use this test to measure intraoperative airborne microbe-carrying-particle sterile-field contamination and compare it with ultraclean-air reference levels for environmental quality-control programs.